Practice of Transformational Leadership of School Heads and Work Performance of Teachers in Public Elementary Schools - Esogon, Stephanie Grace; Gumban, Joey; Guitche, Melona (Journal of Interdisciplinary Perspectives, 2024)
Good leadership is significant since it is one of the motivating factors that motivate teachers to excel in providing quality education to learners. The purpose of this study is to measure the extent of the practice of transformational leadership of school heads and the work performance of teachers in public elementary schools in District V of the Division of Bacolod City. Random sampling was used to identify the 175 respondents. The study utilized descriptive, comparative, and correlational research designs and an adapted researcher-made survey questionnaire, which was validated and underwent reliability tests. The research found that school heads were perceived to have a high level of transformational leadership practice and were rated very high by Master and Grade 2 Teachers. Teachers' performance was generally outstanding, except for Grade 2 Teachers, who had very satisfactory ratings. The study concluded that there was no significant difference in leadership practices and work performance according to variable length of service, teaching position, marital status, and grade level taught. Furthermore, no significant relationship was found between the transformational leadership of school heads and teachers' work performance. Research indicates that elementary school teachers assessed their school heads as transformational leaders, and teachers demonstrated a high level of work performance. In conclusion, despite the positive effects of transformational leadership on motivation at work, it does not significantly impact teachers' performance. Thus, factors such as teaching styles and classroom strategies may significantly influence work performance.